Analisis Kelayakan Novel “Hafalan Shalat Delisa” Karya Tere Liye sebagai Bahan Pembelajaran Bahasa dan Sastra Indonesia di SMA - Henri Henriyan Al Gadri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
This study discusses the feasibility analysis of the Novel "Hafalan Shalat Delisa" by Tere Liye as a teaching material in high school. The purpose of this research is to know the value of character education in the novel "Hafalan Shalat Delisa" as a consideration of the feasibility of Indonesian language learning and literature in high school. The results of this research are the Novel "Hafalan Shalat Delisa" by Tere Liye can be used as a material for learning Indonesian language and literature in school because it is seen from values, in the Novel has the values of goodness for its readers. One of the values of character education consists of religious, reading, social care, national spirit, love of peace, honest, hard work, independent, and responsibility. Also, the Novel "Hafalan Shalat Delisa" fulfills on Valid criteria, beneficial, interesting, and has the boundaries of ability